Philosophy of anthropology and sociology - Turner, Stephen P., 1951-; Risjord, Mark W., 1960- (Handbook of the philosophy of science., 2007)
This volume concerns philosophical issues that arise from the practice of anthropology and sociology. The essays cover a wide range of issues, including traditional questions in the philosophy of social science as well as those specific to these disciplines. Authors attend to the historical development of the current debates and set the stage for future work. Comprehensive survey of philosophical issues in anthropology and sociology Historical discussion of important debates Applications to current research in anthropology and sociology.